Milne Fiord currents from ADCP (Acoustic Doppler Current Profiler) ... - Hamilton, Andrew; Mueller, Derek; Bonneau, Jérémie; Laval, Bernard (Canadian Cryospheric Information Network, 2024)
Ocean currents in Milne Fiord were measured using ADCP (Acoustic Doppler Current Profiler). An ADCP was deployed in the middle of the fjord for 3 days in May 2013 and 4 days in July 2012. In July 2013, two ADCP were deployed, the first (top) for 10 days and the second for 7 days (bottom). The measurements show that along-fjord and across-fjord velocities have similar amplitude. The maximum velocity magnitude recorded is 5 cm/s. The stronger currents are situated around 50 m depth. ... : Measure ocean currents in Milne Fiord, Nunavut, Canada. ...